Effect of beta-carotene on lipid levels in Diet induced hyperlipidemic rats - S. NARAYANASAMY; S. PADMAVATHI; MR.SABARI SELVAN; G.SOMASUNDARAM (International Journal of Pharma and Bio Sciences, 2017)
This study attempt to evaluate the effect of beta-carotene in lipids level in diet induced hyperlipidemic rats. The rats were randomly divided into three groups of 6 animals each. Group 1 Normal control, Group II as positive control and Group III as test group. Blood samples were collected to perform lipid profile analysis. HDL levels significantly increased (51.50±3.94) and LDL levels reduced in test group (73.33±4.84) when compared to the control group. Atherogenic index (0.11±0.04), MDA (5.40±0.32) and Total cholesterol/HDL ratio (3.06±0.31) and TGL/HDL ratio (2.99±0.27) were also significantly reduced. Beta-carotene showed positive cardio protective effect by improving HDL value and reducing TAG/HDL ratio, atherogenic index and LDL cholesterol. Our results support the claim of the researchers who have found beta carotene administration to be effective in improving dyslipidemia. But further studies can be designed to test the effectiveness of beta carotene at various doses.